2016
DOI: 10.1080/1081602x.2016.1224729
|View full text |Cite
|
Sign up to set email alerts
|

Family structure and childhood anthropometry in Saint Paul, Minnesota in 1918

Abstract: Concern with childhood nutrition prompted numerous surveys of children’s growth in the United States after 1870. The Children’s Bureau’s 1918 “Weighing and Measuring Test” measured two million children to produce the first official American growth norms. Individual data for 14,000 children survives from the Saint Paul, Minnesota survey whose stature closely approximated national norms. As well as anthropometry the survey recorded exact ages, street address and full name. These variables allow linkage to the 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…There is also evidence that sibship size stunted the growth of British children also in the second half of the twentieth century (Kuh and Wadsworth 1989). In continental Europe most studies also document an historical negative association between family size and height, with evidence coming from East Germany (Baten and Böhm 2010), France (Olivier and Devigne 1983), Italy (Mazzoni et al 2017), Sweden (Cernerud 1993), the Netherlands (Bras et al 2010;Stradford et al 2017;Van Bavel et al 2011), and also outside Europe, in the United States (Roberts and Warren 2017). Beyond the historical literature, there is also evidence that in more recent decades sibship size is also negatively associated with children's growth in the developing countries (Desai 1995;Jordan et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence that sibship size stunted the growth of British children also in the second half of the twentieth century (Kuh and Wadsworth 1989). In continental Europe most studies also document an historical negative association between family size and height, with evidence coming from East Germany (Baten and Böhm 2010), France (Olivier and Devigne 1983), Italy (Mazzoni et al 2017), Sweden (Cernerud 1993), the Netherlands (Bras et al 2010;Stradford et al 2017;Van Bavel et al 2011), and also outside Europe, in the United States (Roberts and Warren 2017). Beyond the historical literature, there is also evidence that in more recent decades sibship size is also negatively associated with children's growth in the developing countries (Desai 1995;Jordan et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Thinness is an indicator of recent undernutrition and eating disorders and often is associated with physical, mental, and intellectual development problems, as well as a higher risk of metabolic disease in adulthood [ 8 10 ]. Families play a vital role in the intervention of children with undernutrition, and studies have reported that family structure affects childhood physical development [ 11 – 13 ]. In one-child families, parents and grandparents pay all their attention to their single child or grandchild.…”
Section: Introductionmentioning
confidence: 99%
“…The argument is mainly based on the relation between sibship size, income and nutritional dilution, crowding and the higher chances of infection in larger families (Bailey, Hatton, & Inwood, 2016;Hatton, 2017). Yet results are mixed: some studies found a significant negative effect of the number of siblings on the height of individuals (De Keyser & Van Rossem, 2017;Mazzoni, Breschi, Manfredini, Pozzi, & Ruiu, 2017;Myrskylä, Silventoinen, Jelenkovic, Tynelius, & Rasmussen, 2013;Roberts & Warren, 2017;Stradford, van Poppel, & Lumey, 2017), while others found effects which are weak or disappear over time (Beekink & Kok, 2017;Öberg, 2015;Poulain, Chambre, Herm, & Pes, 2017;Ramon-Muñoz & Ramon-Muñoz, 2017). The latter argued that the changing role of sibship size could be caused by fertility decline, the general improvement of standards of living, the development of the welfare state, and improving health.…”
Section: Introductionmentioning
confidence: 99%